Footprint and detectability of a well leaking CO2 in the Central North Sea: Implications from a field experiment and numerical modelling. (May 2019) - Vielstädte, Lisa; Linke, Peter; Schmidt, Mark; Sommer, Stefan; Haeckel, Matthias; Braack, Malte; Wallmann, Klaus
Highlights: CO2 gas bubbles are completely dissolved within 2 m above the seabed. CO2 is not emitted into the atmosphere but retained in the North Sea. Dissolved CO2 is rapidly dispersed by tidal currents in the North Sea. Harmful effects on benthic biota occur in the direct vicinity of the leak. Monitoring has to be performed at the seabed and close to the leak. Abstract: Existing wells pose a risk for the loss of carbon dioxide (CO2 ) from storage sites, which might compromise the suitability of carbon dioxide removal (CDR) and carbon capture and storage (CCS) technologies as climate change mitigation options. Here, we show results of a controlled CO2 release experiment at the Sleipner CO2 storage site and numerical simulations that evaluate the detectability and environmental consequences of a well leaking CO2 into the Central North Sea (CNS). Our field measurements and numerical results demonstrate that the detectability and impact of a leakage of <55 t yr −1 of CO2 would be limited to bottom waters and a small area around the leak, due to rapid CO2 bubble dissolution in seawater within the lower 2 m of the water column and quick dispersion of the dissolved CO2 plume by strong tidal currents. As such, the consequences of a single well leaking CO2 are found to be insignificant in terms of storage performance. Only prolonged leakage along numerous wells might compromise long-term CO2 storage and may adversely affect the local marine ecosystem. Since many abandoned wells leak natural gas into the marine environment, hydrocarbon provinces with a high density of wells may not always be the most suitable areas for CO2 storage.